Analisis Penerapan PSAK No.16 Dalam Perlakuan Akuntansi Aset Tetap Pada Koperasi - Syahputra, Ari; Sidauruk, Alden David Mekar; Damanik, Ayu Zurlaini (Accounting Progress, 2024)
Fixed asset accounting is very important for the fairness of the presentation of fixed assets in financial statements. Errors in assessing fixed assets will result in quite material errors because the investment value invested in fixed assets is relatively large. The objective of the research was to analyze the application of Indonesian Financial Accounting Standards (IFAS or PSAK) No.16 in the accounting treatment of fixed assets in cooperatives. The research used descriptive research. The research subject is KSP KOPDIT CU Hidup Baru Tebing Tinggi and the research object is the accounting treatment of fixed assets. The result of the research showed that the accounting treatment of fixed assets at KSP KOPDIT CU Hidup Baru as a whole is in accordance with the Indonesian Financial Accounting Standards (IFAS or PSAK) No.16, but in terms of depreciation of fixed assets, especially assets whose book value has expired, but which can still be used is not reassessment of both its economic value and useful life (indirectly the depreciation method) so that assets always reflect their economic benefits.